Formation of the Scientific School of V. S. R ozhnov in the Field of Digitalization and Automation Accounting - O. V. Rozhnova (Учёт. Анализ. Аудит, 2022)
The article examines automation of Russian accounting, which continued to develop rapidly in 21st century and turned into a new hypostasis of digitalization. It is impossible to overstate contribution of scientists, who stood at the origin of development of the modern economic information environment. The leading role was held by representatives of the scientific school of Moscow Finance Institute (the Finance Academy). Not only did they develop the fundamental and applied Russian accounting science, but also formed the framework that became the foundation for digitalization of accounting. The aim of the article is the study of scientific heritage of the generation of pioneers in accounting automation personified by Professor Vladimir Sergeevich Rozhnov, who was a typical representative of the Soviet scientific school with his scientific personality, breadth of views and interests, and position. The article reveals milestones in the formation of Professor V. S. Rozhnov’s scientific views: the family, ever supportive of his professional endeavors, the environment of the Moscow Finance Institute, which brought up his character as a researcher who cannot be stopped by obstacles, the community of both Soviet and foreign scientists, working in the field of economics, statistics, cybernetics, mechanization and automation of accounting. The scientific cognition methods were used in the article: deduction, induction, analogy and abstraction, synthesis and analysis, including aspect and empirical methods, etc. The article describes the process of formation of scientific schools in Russian universities (with the example of the Finance University); the link of scientific generations, the memory of pioneers in science.